Broad-band properties of flat-spectrum radio-loud narrow-line Seyfert 1 galaxies - Foschini, Luigi; Kaufmann, Sarah (Arxiv, 2016)
We report about recent updates of broad-band properties of radio-loud narrow-line Seyfert 1 galaxies.
Gesehen am 11.10.2017